2015
DOI: 10.1042/bsr20150194
|View full text |Cite|
|
Sign up to set email alerts
|

MELK-T1, a small-molecule inhibitor of protein kinase MELK, decreases DNA-damage tolerance in proliferating cancer cells

Abstract: Protein kinase MELK has oncogenic properties and is highly overexpressed in some tumors. In the present study, we show that a novel MELK inhibitor causes both the inhibition and degradation of MELK, culminating in replication stress and a senescence phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 40 publications
5
75
0
Order By: Relevance
“…4,5 Maternal embryonic leucine zipper kinase (MELK) is a member of the AMP protein kinase (AMPK) family of serine/threonine kinases, and MELK activates multiple cellular pathways that drive oncogenic growth. [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Maternal embryonic leucine zipper kinase (MELK) is a member of the AMP protein kinase (AMPK) family of serine/threonine kinases, and MELK activates multiple cellular pathways that drive oncogenic growth. [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL). [8][9][10][11][12][13] It has been shown that MELK is overexpressed in multiple human tumours, including the following: melanoma, 8 diffuse intrinsic pontine glioma (DIPG), 14 breast cancer, 6,15 gastric cancer, 16 high-grade prostate cancer, 17 hepatocellular carcinoma, 18 kidney cancer, 19 small lung cancer, 20 myeloma, 21 acute myeloid leukaemia (AML) 22 and chronic lymphocytic leukaemia (CLL).…”
Section: Introductionmentioning
confidence: 99%
“…19,[22][23][24][25] A number of studies have shown that MELK inhibition also increases sensitivity to radiation and chemotherapy in pre-clinical adult cancer models, suggesting that combination treatments may also be effective strategies. 13,23,25,[30][31][32] OTSSP167, a type I kinase inhibitor, is an inhibitor that markedly suppresses MELK kinase activity by phosphorylating the MELK substrates DBNL and PSMA1. 13,23,25,[30][31][32] OTSSP167, a type I kinase inhibitor, is an inhibitor that markedly suppresses MELK kinase activity by phosphorylating the MELK substrates DBNL and PSMA1.…”
Section: Introductionmentioning
confidence: 99%
“…However, several discrepancies exist in the literature on MELK. For instance, various publications disagree over the cell cycle stage affected by MELK inhibition (Du et al, 2014; Kig et al, 2013; Alachkar et al, 2014; Wang et al, 2014; Beke et al, 2015), while other publications disagree over whether receptor-positive breast cancer cell lines are sensitive (Lin et al, 2007; Beke et al, 2015; Chung et al, 2012) or resistant (Wang et al, 2014) to MELK inhibition. To unambiguously determine the effects of MELK loss in cancer cell lines, we applied CRISPR/Cas9 to generate frameshift mutations in the MELK coding sequence.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, MELK has been identified as a key driver of basal-type breast cancer, suggesting a novel therapeutic approach to treat this disease (Wang et al, 2014). In response to the widespread reports that MELK is a cancer dependency, several companies have developed small molecule inhibitors of MELK that block the activity of the kinase in vitro and that inhibit cancer cell proliferation at micromolar or nanomolar concentrations (Beke et al, 2015; Touré et al, 2016; Johnson et al, 2015a, 2015b; Chung et al, 2012). Additionally, four clinical trials have been launched to test the MELK inhibitor OTS167 in human cancers (NCT01910545, NCT02768519, NCT02795520, and NCT02926690).…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, activates ATM, Chk2, and p53 sequentially causing cell-cycle arrest and accumulation of DNA damage at stalled replication forks. This same group subsequently demonstrated a similar mechanism when treating with a novel MELK inhibitor (upregulation of p21 leading to activation of ATM, Chk2, and p53) allowing the cancerous cells to continue proliferation in the presence of replicative stress (37,38). It is unclear what, if any, role this mechanism plays in radioresistance of triple-negative and basal-like breast cancers as the vast majority of these tumors, and all of the cell lines used in this study, harbor p53 mutations.…”
Section: Discussionmentioning
confidence: 96%